What sticks? Patients' perspectives on treatment three years after psychotherapy: A mixed-methods approach. (17th August 2020) - Wucherpfennig, Felix; Boyle, Kaitlyn; Rubel, Julian A.; Weinmann-Lutz, Birgit; Lutz, Wolfgang
Abstract: Objective: In the present study, a patient-focused, mixed-methods approach was applied to relate patients' personal experiences of change processes during therapy to their long-term psychometric treatment outcomes. Method: Comprehensive follow-up quantitative assessments and qualitative interviews were conducted with n = 30 patients who had completed an integrative CBT treatment three years prior. Qualitative content analysis by two independent coders was used to categorize patients' subjective explanations of therapeutic change. Correlations were applied to relate the frequency and diversity of change factors to clinically significant change of symptom distress at post-treatment and 36-month follow-up. Cluster analysis was performed to identify clusters of patients with similar patterns of change factors. Results: Qualitative content analysis with good interrater reliability revealed five main categories: (1) Therapeutic relationship (2) Activating resources (3) Motivational clarification and insight (4) Action-oriented coping strategies (5) Healing therapeutic setting . Higher levels of change factors were associated with greater relief of symptoms at post-treatment and 36-month follow-up. Cluster analysis revealed three different groups of patients. Conclusions: The analysis provides insight into therapeutic change factors from the patient's perspective. Some categories are consistent with theoretically driven models of common factors. Results may help tailor psychotherapy to patients' individual needs.